2012
DOI: 10.1016/j.ccr.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Redirects Glucose and Glutamine into Anabolic Pathways in Metabolic Reprogramming

Abstract: Cancer cells consume large quantities of nutrients and maintain high levels of anabolism. Recent studies revealed that various oncogenic pathways are involved in modulation of metabolism. Nrf2, a key regulator for the maintenance of redox homeostasis, has been shown to contribute to malignant phenotypes of cancers including aggressive proliferation. However, the mechanisms with which Nrf2 accelerates proliferation are not fully understood. Here, we show that Nrf2 redirects glucose and glutamine into anabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
1,225
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,194 publications
(1,279 citation statements)
references
References 47 publications
45
1,225
5
4
Order By: Relevance
“…1A,B). Twenty-four of 25 Nrf2 mutations were located in the Nrf2 regions coding for either the LxxQDxDLG motif (spanning amino acids [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] or the DxETGE motif (amino acids 77-82) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…1A,B). Twenty-four of 25 Nrf2 mutations were located in the Nrf2 regions coding for either the LxxQDxDLG motif (spanning amino acids [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] or the DxETGE motif (amino acids 77-82) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…An antineoplastic compound, brusatol, is an Nrf2 inhibitor that increases the chemotherapeutic efficacy of cisplatin, a common chemotherapeutic (Ren et al 2011). PI3K inhibitors (Mitsuishi et al 2012) and Nrf2 siRNA inhibit Nrf2 in cancer cells. Cancer suicide gene therapy, which is an alternative approach, has been utilised to target the cancer cells with high Nrf2 levels.…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…Also, other metabolic genes, including malic enzyme 1 (ME1), pyrophosphate phosphoribosyl amidotransferase (PPAT), methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) and isocitrate dehydrogenase 1 (IDH1), were also identified as transcription targets of Nrf2. These proteins are responsible for purines synthesis, which are the building blocks of DNA and RNA, which in turn, leads to the proliferation of cancer cells (Mitsuishi et al 2012). Several studies have shown that elevated levels of Nrf2 in cancer cells are less sensitive to chemotherapeutic treatments and renders more resistant to cancer cells against a variety of anti-cancer agents (Shibata et al 2008a, b;Wang et al 2008).…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…G6PD is a rate‐limiting enzyme of PPP which activates this pathway in response to the breakdown of NADPH (Ben‐Yoseph et al., 1996). In addition, G6PD is one of the biological protective factors orchestrated by Nrf2 (Mitsuishi et al., 2012), which is a transcriptional factor that ubiquitously responds to various physiological and pathological conditions.…”
Section: Resultsmentioning
confidence: 99%